Análise de compostos fenólicos e atividade antioxidante nas etapas da produção de cerveja - Couto, Adriana Maria Leuzzi de Castro (2023)
In recent years, the nutritional interest of beer has increased because it is a product rich in compounds with antioxidant properties. Studies on antioxidants, especially phenolic compounds from beer and raw materials, have been increasingly explored. Beer phenolics are mainly derived from barley malt, followed by hops, due to their ratios used in brewing. However, the dry-hopping technique and fruit addition can be good alternatives to increase the bioavailability of phenolics in beer, benefits both for its stability and for the health of the consumer, since they are products rich in bioactive compounds. Considering the above, the objective of this study was to produce beers with a high phenolic content and high antioxidant capacity. The work was divided into two stages, with the aim of evaluating the raw materials (malts and yeasts) that would bring the best results in terms of phenolics and antioxidant capacity and, subsequently, improving these results with the increment of strawberries and hops using the dry hop technique. The beers were produced with 100% Pilsen barley malt and with Pilsen barley malts and wheat malt in a 50:50 ratio. During the beer mashing, the samples were collected after temperature ramps, from the lowering (moment when we added the ground malt to the water) until the end of the boil. For tests with Lager yeast, temperatures of 12 °C were used for fermentation, 8 °C for fermentation and 0 °C for clarification. For the tests with Ale yeast, temperatures of 20 °C were used for fermentation, 12 °C for maturation and 0 °C for clarification. Physical-chemical analyzes (pH, density, sugars and total phenolics) were carried out on samples collected during the mashing process, after fermentation, maturation and clarification. The best result of total phenolics was obtained in the first stage of the beer produced with barley Pilsen malt and Lager yeast. Then, we proceeded to the second stage of the process by adding the strawberry and hops during fermentation. The sampling took place similar to the first stage, but it was also taken during fermentation, before adding the fruit and performing dry hopping. The best results in relation to the total phenolic content and the total amount of antioxidants were obtained in the beers produced with barley Pilsen malt, bottom fermentation yeast and addition of strawberries and hops by dry hopping in the fermentation stage, thus proving the enrichment of bioactive compounds that can increase its shelf life and consumer health.